Enhanced high hydrostatic pressure lethality in acidulated raw pet food formulations was pathogen species and strain dependent. (June 2022) - Serra-Castelló, Cristina; Possas, Aricia; Jofré, Anna; Garriga, Margarita; Bover-Cid, Sara
Abstract: Feeding dogs and cats with raw meat-based pet food is taking relevance in the recent years. The high aw of these products together with the no cooking before its consumption by the animal pose a risk due to the potential occurrence and growth of foodborne pathogens. High pressure processing (HPP) is a non-thermal emerging technology that can be used as a lethality treatment to inactivate microorganisms with a minimum impact on the sensory and nutritional traits of the product. The purpose of the present study was to evaluate the variability in pressure resistance of different strains of the relevant foodborne pathogens Salmonella spp., Escherichia coli and Listeria monocytogenes in raw pet food formulated without and with lactic acid. In general, Salmonella and L. monocytogenes strains showed a higher resistance to HPP than E. coli strains. In lactic acid acidulated formulations, the susceptibility to HPP of L. monocytogenes was markedly enhanced. The resistance to HPP was not only dependent on the microorganism but also on the strain. Thus, the selection of the proper strains should be taken into account when designing and validating the application of HPP as a control measure within the HACCP plan. Highlights: HPP-resistance variability among pathogenic strains was assessed in raw pet food. Salmonella and L. monocytogenes strains showed higher resistance than E. coli . Enhanced lethality in acidulated formulations was species and strain dependent. Sublethal injury can let to an overestimation of HPP lethality.